Coping Stress pada Istri yang Menjalani Long Distance Married - Mulya Virgonita Iswindari Winta; Retno Dwi Nugraheni (Philanthropy: Journal of Psychology, 2019)
Abstract. This study aims to determine how the image of coping stress on wives undergoing long distance marriage. This research uses qualitative methods, phenomenology. The subjects in this study were three people and used six research informants. The results showed that the three subjects had different coping stress images depending on how the situation was being faced. The three subjects combined emotional focused coping and problem focused coping in dealing with stress, using an active approach, both by taking action to reduce stressors and manage emotions and thoughts. Found two subjects using coping that is less healthy and less constructive, causing new problems that aggravate the situation. Found other factors that cause stress on wives who undergo long distance married. Keywords: Coping stress, Long distance relationship, MarriageDaftar PustakaBaqutayan, S.M.S. (2015). Stress and coping mechanism: a Historical Overview. Mediterranean Journal of Social Science. Vol 6 No 2 S1: 479 488Creswell, J. (2015). Penelitian Kualitatif & Desain Riset. Yogyakarta: Pustaka PelajarFeldman, R. S. (2012). Pengantar Psikologi. Jakarta: Salemba Humanika.Gaol, N.T.L. (2016). Teori Stres: Stimulus, Respons dan Transaksional. Buletin Psikologi 2016 Vol 24, No 1, 1 11. DOI: 10.22146/bpsi.11224Handayani, Y. 2016. Komitmen, Conflict Resolution dan Kepuasan Perkawinan pada Istri yang Menjalani hubungan Pernikahan Jarak Jauh. Psikoborneo. 4(6), 518 - 529Lestari, D. W. (2014). Penerimaan dan Strategi Coping pada Remaja Korban Perceraian Orang Tua . eJournal Psikologi, Vol. 2, No. 1, hlm. 1-13.Mashudi, D. (2012). Psikologi Konseling. Jogjakarta: IRCiSoD.Mijilputri, N. (2015). Peran Dukungan Sosial Terhadap Kesepian Istri yang Menjalani Hubungan Pernikahan Jarak Jauh (Long Distance Marriage) . eJournal Psikologi, Vol. 3, No. 2, hlm. 477-491.Naibaho, S. L. dan Virlia, S. (2016). Rasa Percaya pada Pasutri Perkawinan Jarak Jauh . Jurnal Psikologi Ulayat, Vol. 3, No.1, hlm. 34-52.Nuraini, F.D. dan Masykur, A.M. (2015). Gambaran Dinamika Psikologis pada Istri Pelaut. Jurnal Empati. (2015). Volume 4 (1), 82 - 87Papalia, D. E, Old, W. S., &., Feldman, R. D., (2009). Human Development "Perkembangan Manusia"Edisi 10 Jilid 2. Jakarta: Salemba Humanika.Poerwandari, K.E. (2011). Pendekatan Kualitatif dalam Penelitian Psikologi. Jakarta: LPSP3 Psikologi UIPraweswara, A.D. dan Sakti, H. (2016). Pernikahan Jarak Jauh ( Studi Kualitatif Fenomenologis pada Istri yang Manjalani Pernikahan Jarak jauh). Jurnal Empati, Agustus 2016, Volume 5(3), 417 423Ramadhini, S. dan Hendriani W. (2015). Gambaran Trust pada Wanita Dewasa Awal yang sedang Menjalani Long Distance Married. Jurnal Psikologi Klinis & Kesehatan Mental. Vol 4 No 1 April 201, 15 - 20Safaria, T., & Saputra, N. E. (2009). Manajemen Emosi: Sebuah Panduan Cerdas Bagaimana Mengelola Emosi Positif Dalam Hidup Anda. Jakarta: Bumi Aksara.Srisusanti, S dan Zulkaida, A. (2013). Studi Deskriptif Mengenai Faktor-Faktor yang Mempengaruhi Kepuasan Perkawinan pada Istri. UG Jurnal Vol 7 No 6 Tahun 2013, 8 12  Stroebe, W. (2011). Social Psychology and Health. New York: McGraw-Hill.  Suminar, J.R. dan Kaddi, S.M. (2018). The Phenomenon of Married Couples with Long-Distance Married. Mimbar: Jurnal Sosial dan Pembangunan. Volume 34 Nomor 1 June 2018, pp. 121 129  Winta, M.V.I. dan Syafitri, A.K. (2019). Coping Stress pada Ibu yang Mengalami Kematian Anak. Philanthropy: Journal of Psychology. Vol 3 No 1, 2019, 14-33